Bent spine syndrome as the initial symptom of late‐onset Pompe disease. Issue 1 (30th November 2016) - Taisne, Nicolas; Desnuelle, Claude; Juntas Morales, Raul; Ferrer Monasterio, Xavier; Sacconi, Sabrina; Duval, Fanny; Sole, Guilhem; Flipo, René Marc; Lacour, Arnaud; Vermersch, Patrick; Cardon, Thierry
ABSTRACT: Introduction : Late‐onset Pompe disease (LOPD) is a rare disorder characterized by progressive proximal muscle weakness and early respiratory insufficiency, for which enzyme replacement therapy (ERT) is available. Methods : Having diagnosed a case of LOPD presenting with bent spine syndrome, we conducted a brief survey in the French centers involved in management of Pompe disease, from which we collected data on 3 other cases. Results : The patients (3 women and 1 man) had a mean age of 64 years (range 51–77 years) and a delay in diagnosis of approximately 10 years (range 8–42 years). At diagnosis, 3 patients already had respiratory symptoms. All had normal or very mildly raised creatine kinase levels and magnetic resonance imaging abnormalities in the paraspinal muscles. They exhibited the most frequent mutation in Pompe disease (c.‐32‐13 T>G). Conclusion : Clinicians should be aware of this atypical presentation of LOPD to enable earlier diagnosis and treatment. Muscle Nerve 56 : 167–170, 2017